Le développement de la graphique de 1967 à 1997 - Serge Bonin (Cybergeo, 2000)
The Graphic Semiology was published in 1967. Thirty years ago. The Laboratory of Cartography of the 6th section of the Ecole Pratique des Hautes Études had existed for a dozen years; Created by Lucien Febvre and supported by Fernand Braudel, presidents of the institution, Jacques Bertin was its director. Since then, the 6th section of the École Pratique des Hautes Études has become the École des Hautes Etudes en Sciences Sociales, and the Laboratory of Cartography, a service laboratory, has become the Laboratoire de Graphique, a research laboratory. Thirty-seven years of activity in the laboratory, including nearly thirty past Jacques Bertin, allow me to reflect on the development of graphics, to make an assessment from the inside.